Early Children (3;0–5;0) are Affected by Their Mastery of Indonesian Vocabulary the Environment's Intake - H. Syanurdin; Nanda Saputra; Herman Herman; Heni Novita Sari (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study attempts to examine and describe how parents' social position and surroundings can affect their children's vocabulary competence when learning Indonesian. Based on behaviorism theory's tenets, which are also backed by cognitivism theory. According to this hypothesis, a child's (exogenous) environment has a significant impact on their ability to acquire a language, particularly when it comes to developing their vocabulary. Both of these strands categorically rejected Nativism, which maintained that the ability to speak a language is an innate and biological gift (LAD). The mastery of children's linguistic vocabulary is thought to be unaffected by the surroundings. This study analyzes, but it also demonstrates how the environment affects young children's language and vocabulary development 3;0-5;0 at the Bustanul Athafal Early Childhood Education, Singgaran Pati District, Bengkulu City, TA. 2020/2021. The results showed that the influence of environmental intake on children's Indonesian vocabulary mastery was calculated by product-moment correlation and then used the formula: d = r². 100% obtained value = 0.49%. This means that the magnitude of the influence of environmental (exogenous) intake on children's mastery of Indonesian vocabulary is 49% and 51% is influenced by endogenous factors.